If it's not what You are looking for type in the equation solver your own equation and let us solve it.
X-4-2=X-12
We move all terms to the left:
X-4-2-(X-12)=0
We add all the numbers together, and all the variables
X-(X-12)-6=0
We get rid of parentheses
X-X+12-6=0
We add all the numbers together, and all the variables
6!=0
There is no solution for this equation
| 4x+53x-2=24 | | (3-4m)=21 | | 0.18x+0.4(x-5)=0.01(8x-7) | | g(-3)=2(-3)^2-5 | | (3x-2)/21+X=(3x+2)/3+2 | | 7/x4-5=5x/4+3 | | 6r/5=36 | | 5x-2+2x+3=44 | | 8(3z-2)=32 | | 0.025p-1=0.15(p-5) | | 8(3z-20=32 | | 19=7z+1-5z | | 22(x-5)+2x=4(x+2)-18 | | x^2-27x+130=0 | | x^2-27x+130)=0 | | k+19=-1 | | -3(-6y+5)-6y=2(y-8)-3 | | -2=10-4-7x | | (5×+2y=-13) | | -2(p-5)+7p=23 | | 7.x+8=57 | | -4(v-8)=2v+8 | | 21=u/2-16 | | 16=3u-14 | | 4x/3x=-1 | | d12=6 | | 3(2x-2)=-2(x+3)+12 | | 35x^2+40x=0 | | 3(x-2)+7=19 | | 12=15(z−1/5 ) | | 30=2x^2+12-50 | | 3x^2+40x=0 |